Use of Essential Oils to Counteract the Phenomena of Antimicrobial Resistance in Livestock Species - Carmine Lupia; Fabio Castagna; Roberto Bava; Maria Diana Naturale; Ludovica Zicarelli; Mariangela Marrelli; Giancarlo Statti; Bruno Tilocca; Paola Roncada; Domenico Britti; Ernesto Palma (MDPI AG, 2024)
Antimicrobial resistance is an increasingly widespread phenomenon that is of particular concern because of the possible consequences in the years to come. The dynamics leading to the resistance of microbial strains are diverse, but certainly include the incorrect use of veterinary drugs both in terms of dosage and timing of administration. Moreover, the drug is often administered in the absence of a diagnosis. Many active ingredients in pharmaceutical formulations are, therefore, losing their efficacy. In this situation, it is imperative to seek alternative treatment solutions. Essential oils are mixtures of compounds with different pharmacological properties. They have been shown to possess the antibacterial, anti-parasitic, antiviral, and regulatory properties of numerous metabolic processes. The abundance of molecules they contain makes it difficult for treated microbial species to develop pharmacological resistance. Given their natural origin, they are environmentally friendly and show little or no toxicity to higher animals. There are several published studies on the use of essential oils as antimicrobials, but the present literature has not been adequately summarized in a manuscript. This review aims to shed light on the results achieved by the scientific community regarding the use of essential oils to treat the main agents of bacterial infection of veterinary interest in livestock. The Google Scholar, PubMed, SciELO, and SCOPUS databases were used for the search and selection of studies. The manuscript aims to lay the foundations for a new strategy of veterinary drug use that is more environmentally friendly and less prone to the emergence of drug resistance phenomena.